Native Strains T. longibrachiatum UCF17-M4 and Trichoderma sp. UCPF2 Reduce Cd Uptake in Cacao CCN51 Under Controlled Conditions - Rozana Yanina Malca-Cerna; Cortez-Lazaro Anthony Apolinario; Chavez-Castillo Jeremy Israel; Arce-Inga Marielita; Cumpa-Velasquez Liz Marjory (Microbiology Research)
The cacao trade and export industry has been impacted by cadmium (Cd2+) accumulation in soils, as the metal is absorbed by plants and transferred to the tissues. Consequently, cacao beans and their derivatives can become contaminated, sometimes exceeding permissible limits. In this study, the capacity of native Trichoderma strains to reduce Cd accumulation in cacao was evaluated. Twelve Trichoderma strains were analyzed to assess their cadmium removal capacity through in vitro assays and their ability to reduce Cd concentration in cacao plants under controlled in vivo conditions. The in vitro results showed that several Trichoderma strains could remove cadmium and accumulate it in their biomass. However, this process is complex as it depends on metal concentration and environmental conditions. Notably, T. afroharzianum UCF18-M1 and CP24-6 exhibited high removal efficiencies at 100 ppm (61.79 ± 2.98% and 57.93 ± 4.14%, respectively). In contrast, the in vivo assays revealed that, contrary to expectations, some strains—including those with the highest removal efficiency—stimulated Cd uptake in plants, even at toxic levels, such as T. orientale BLPF1-C1. However, T. longibrachiatum UCF17-M4 and Trichoderma sp. UCPF2-C1 significantly reduced Cd accumulation in the stem. These findings highlight the potential of these strains to mitigate Cd contamination in cacao.